Arabic Language Learning Activities for Early Childhood Using Habit-Formation and Singing Methods - Ramadhani, Dinda Asri; Zein, Azizah; Putri, Leoni Sabrillina; Lubis, Hilda Zahra (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to explore the effectiveness of the habit-formation and singing method in learning Arabic for early childhood at TK IT Bunayya 7. With a descriptive qualitative approach, this study observed the learning activities carried out by teachers and the interactions of children during the learning process. The habit-formation method was applied through repetition of simple vocabulary and phrases in daily activities, while the singing method was used to introduce vocabulary and sentence structures in a fun way. The results showed that the combination of these two methods succeeded in creating an interactive and fun learning atmosphere, increasing children's memory of Arabic vocabulary, and building their confidence in using the language. This study concluded that the application of the habituation and singing method was not only effective in language acquisition, but also supported children's psychological development, making it a learning model that is worthy of being applied in early childhood education.